FACE VALUES: LEADERSHIP THE GIANFRANCO ZOLA WAY. Issue 3 (10th September 2013) - Dearlove, Des
Abstract : Currently manager of Watford FC, Gianfranco Zola was one of the greatest Italian football players to grace the English Premier League. Born in Sardinia in 1966, he spent the first decade of his career playing in Italy, most notably with Napoli, where he played alongside the legendary Argentinian Diego Maradona and Brazilian striker Careca, and at Parma, before moving to Chelsea in November 1996.